The Moderating Effect of Organizational Identification on the Relationship Between Organizational Role Stress and Job Satisfaction - Eriş, Abdullah; Kökalan, Özgür (Frontiers in Psychology, 2022)
This study aims to investigate the moderating effect of the organizational identification level of the employees on the relationship between their organizational role stress level and job satisfaction. The data were gathered from 460 white- collar employees with snowball sampling. Covariance-based structural equation modeling (CB-SEM) was used in data analysis. According to the research results, it was found that there is a significant negative relationship between the organizational role stress level of the employees and their job satisfaction (r=-.486, p< .01). The research also shown that organizational identification had a moderating effect on the negative relationship between organizational role stress and job satisfaction. An employee who has a high level of organizational identification has more job satisfaction than an employee who has less organizational identification.